National Pride Projects in Nepal: Sectoral Priorities and Implementation Gaps (SADGAMAYA, 2026)
In Nepal, National Pride Projects (NPPs) are big, long-term plans that are meant to speed up economic growth, improve infrastructure, make sure energy security, and boost the country's reputation. Even if they are important, there are still worries about how unevenly they are distributed and how slowly they are being put into action. This study examines the sectoral distribution, implementation status, and temporal trends of 27 National Pride Projects in Nepal, employing a descriptive and analytical research design grounded in secondary data. The results show that most of the projects (48.1%) are in the infrastructure sector. This shows that the policy is focused on physical connectivity and economic integration. Energy and agriculture sectors each make up 14.8% of the projects. This shows that there is moderate interest in energy self-sufficiency and food security. On the other hand, there are less projects in the areas of water supply, cultural heritage, and environmental conservation. Most of the projects (70.4%) are still going on, while only 18.5% are finished. This shows a big implementation gap. Cross-tabulation research shows that delays are more common in the agriculture and infrastructure sectors, while energy projects tend to have higher completion rates. The historical analysis reveals a concentration of project initiation at particular intervals, notably in 2068 and 2072 B.S., indicating focused policy impetus but also hinting at possible overextension of administrative and technical resources. The study emphasizes a developmental strategy predominantly dependent on extensive infrastructure, while exposing systemic difficulties associated with project implementation, coordination, and resource allocation. The report indicates that while National Pride Projects embody Nepal's ambitious development vision, enhancing implementation efficiency, balancing sectoral objectives, and bolstering institutional capacity are crucial for ensuring their timely completion and enduring impact.